Pengaruh Konsentrasi Asam Fosfat (H₃PO₄) terhadap Struktur Pori dan Kinerja Adsorpsi Karbon Aktif Kulit Manggis (Garcinia mangostana L.) terhadap Metilen Biru - Rindy Julyantika; Erna Purwantiningtyas; Yuliana Rahman (Pure Chemistry Research, 2026)
Mangosteen peel (Garcinia mangostana L.) is an abundant lignocellulosic biomass waste with a high carbon content, making it a promising precursor for the production of activated carbon. This study aimed to evaluate the effect of phosphoric acid (H₃PO₄) concentration on pore structure development and the adsorption performance of mangosteen peel-derived activated carbon for the removal of methylene blue from aqueous solution. Activated carbon was prepared through carbonization at 500 °C, followed by chemical activation using H₃PO₄ at concentrations of 10%, 20%, 30%, and 40%. The resulting materials were characterized in terms of yield, moisture content, ash content, iodine number, Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and Brunauer–Emmett–Teller (BET) surface area analysis. Adsorption performance was evaluated using batch adsorption experiments, while adsorption equilibrium and kinetics were analyzed using isotherm and kinetic models. The results demonstrated that increasing the H₃PO₄ concentration up to 30% significantly enhanced pore structure development, resultingin a specific surface area of 872 m²/g, a pore volume of 0.47 cm³/g, and an iodine number of 836 mg/g. Under these optimum conditions, the activated carbon achieved a methylene blue adsorption capacity of136 mg/g with a removal efficiency of 84.8%. Statistical analysis revealed that variations in H₃PO₄ concentration significantly affected the adsorption capacity (p = 0.0008). Adsorption equilibrium was best described by the Langmuir isotherm model (R² = 0.978), with a theoretical maximum adsorption capacity of 145.6 mg/g, whereas the adsorption kinetics followed the pseudo-second-order model (R² = 0.986). These findings indicate that chemical activation with 30% H₃PO₄ represents the optimum condition for producing mangosteen peel-derived activated carbon with well-developed pore structures and high adsorption performance, highlighting its potential as an environmentally friendly adsorbent for dye-contaminated wastewater treatment.